Metabolic Changes after Urinary Diversion - Frank Van der Aa; Steven Joniau; Marcel Van Den Branden; Hein Van Poppel (Advances in Urology)
Urinary diversion is performed on a regular basis in urological practice. Surgeons tend to underestimate the metabolic effects of any type of diversion. From the patient's perspective, diarrhea is the most bothersome complaint after urinary diversion. This might be accompanied by malabsorption syndromes, such as vitamin B12 deficiency. Electrolyte abnormalities can occur frequently such as hyperchloremic metabolic acidosis, or less frequently such as hypokalemia, hypocalcaemia, and hypomagnesaemia. Bone health is at risk in patients with urinary diversion. Some patients might benefit from vitamin D and calcium supplementation. Many patients are also subject to urinary calculus formation, both at the level of the upper urinary tract as in intestinal reservoirs. Urinary diversion can affect hepatic metabolism, certainly in the presence of urea-splitting bacteria. The kidney function has to be monitored prior to and lifelong after urinary diversion. Screening for reversible causes of renal deterioration is an integral part of the followup.